Application of Direct Instructional Learning in High School Education - Alimuddin Alimuddin; Suradi; Marina Rahmayanti (HM Publisher, 2021)
A direct teaching model is a teaching approach that can help students learn basic skills and acquire information that can be taught step by step. Direct instruction or direct teaching is based on behavioristic learning theory that focuses on the mastery of concepts and changes in behavior as a result of learning that can be observed. The approach used in this model is teacher-centered. The teacher presents material/transfers information directly and structured using a lecture, expository, question, and answer, presentation/demonstration model. This model is the leading choice applied to students due to its advantages, including the relatively large amount of material delivered, easy learning time to manage, and this model will be relatively easy to follow for procedural matters. In addition to some of its advantages, the direct teaching model also has drawbacks that, according to researchers, are vital to the learning process itself; namely, students tend to wait for raw answers from the material presented by the teacher.